Implementation of C4.5 Agorithm in predicting the timeliness of student graduation (Case Study: Informatics Management Study Program, Labuhanbatu University) - Syaiful Zuhri Harahap; Musthafa Haris Munandar; Masrizal; Ibnu Rasyid Munthe; Meidy Putra Panusunan Siregar (Jurnal Mantik, 2020)
The high success rate of college students and the low student failure rate represent the college's standard. College Student loss and its causal causes are interesting subjects for study. Colleges are actually in a very demanding climate. Any college aims to continually develop its management to improve the quality of its education and improve its accreditation. One feature of the college accreditation examination is time graduation. Also, timely graduation is an essential concern because graduation rates are the foundation for its effectiveness. One of the problems that are now the topic of talking about academic failure is students' dropout and graduation. Data mining is a technique of tracing current data to create a model and then using it to recognize other data patterns not contained in the database. One of the techniques used in data mining is the classification methodology using the C4.5 process.